Management of Student Characteristics Through Extracurricular Activities in The School Environment Based on Islamic Boarding Schools - Ujang Sahid; Iim Wasliman; Hendi Suhendraya Muchtar; Husen Saeful Insan (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2021)
Moral development is the most important thing in education, including in pesantren-based educational institutions. Moral development will be carried out properly if it is carried out in a planned and programmed manner. Moral Development Management for Students Through Extracurricular Activities in Islamic Boarding Schools is one of the best solutions in realizing commendable student morals. This research was conducted to see the extent to which moral development was carried out at Al-Amin Middle School and Al-Ittihad Middle School Cianjur. The theory that forms the basis of the research is the management theory of POAC, TQM, and Six Life Value Systems. This research uses a descriptive qualitative approach. The research findings show that: (1) The management of the moral development program through extracurricular activities is based on the commitment of teachers, parents, and program implementation. (2) The implementation of the moral development program is the most basic principle and serves as a differentiator for the progress and decline of the quality of SMP. This conformity shows that in practice the moral development program through extracurricular activities has not been carried out according to process standards. (3) Evaluation of activities and problems encountered through monitoring and evaluation of the process and achievement of SMP institution development goals. (4) In general, the inhibiting factors in program development, such as curriculum, budget allocation, facilities, and infrastructure. (5) Improvement Efforts, solving problems in quality improvement, one of which is by holding FGD (Focus Group Discussion), workshops, and others.